2014
DOI: 10.1371/journal.pone.0106164
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin Inhibitor Tacrolimus Reduces Proteinuria in Membranous Nephropathy Accompanied by a Decrease in Angiopoietin-Like-4

Abstract: Tacrolimus is an anticalcineurinic agent with potent immunosuppressive activity that has recently been shown to have the added benefit of reducing proteinuria in membranous nephropathy (MN) patients. However, its potential mechanisms remain unknown. To reveal the mechanism, rat cohorts were administered tacrolimus or vehicle from days 7 to 28 after the induction of passive Heymann nephritis (PHN). PHN induction resulted in heavy proteinuria and increased expression of desmin, a marker of injured podocytes. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Moreover, podocyte functional assay also showed increased cell viability and decreased cell motility in CsA and FK506 preincubated podocytes. The protective effects of CaN inhibitors (CsA and FK506) were also observed in other podocyte injury models such as adriamycin induced MCD29, membranous nephropathy4, Lupus Nephritis27 and IgA nephropathy6.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, podocyte functional assay also showed increased cell viability and decreased cell motility in CsA and FK506 preincubated podocytes. The protective effects of CaN inhibitors (CsA and FK506) were also observed in other podocyte injury models such as adriamycin induced MCD29, membranous nephropathy4, Lupus Nephritis27 and IgA nephropathy6.…”
Section: Discussionmentioning
confidence: 68%
“…Simultaneously, PHN rats were chosen as positive control as shown in Supplemental Fig. S1, since significant enhanced Angptl4 expression was observed in PHN rats according to our very recent study [22].…”
Section: Resultsmentioning
confidence: 99%
“…Rat and human kidney tissues were fixed in PLP solution for 2 h, followed by an overnight incubation in 18 % sucrose as our previously described [21,22]. The tissues were then embedded in a Tissue-Tek OCT compound, flash-frozen, and stored at -80°C.…”
Section: Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, according to a study conducted by Pengcheng Zhu et al [21] ANGPTL4 could elevate O 2 -production and O 2 -:H 2 O 2 ratio through stimulating NADPH oxidase 1 (Nox1), which indicates the possible relationship between ANGPTL4 and ROS production. Also, reducing the expression of ANGPTL4 in podocytes could decrease the podocyte apoptosis and promote podocyte repair [22]. These studies indicated that the up-regulated ANGPTL4 was highly related with the ROS production and podocyte apoptosis.…”
Section: Introductionmentioning
confidence: 85%